Pengujian Teori Trade-Off dan Pecking Order: dengan Satu Model Dinamis pada Perusahaan Publik di Indonesia - Darminto, Darminto; Manurung, Adler Haymans (Universitas Prasetiya Mulya, 2008)
This article explores determinant of capital structure in Indonesia. Empirical study using Regression in model is done by including variable suggested by Trade of Theory, Pecking Order Theory, and combination of those theories. The result shows that determinant factors in the Trade of Theory have more ability to explain the capital structure than deficit cash flow factor in pecking order theory. Other variables that are also significant are firm size and collateral capacity. Its is possible that rejection of Pecking Order Theory is due to market timing argument in long term financing.